Нейтронно-активационное определение антропогенных элементов во мхах-биоиндикаторах; Известия вузов. Физика; Т. 53, № 10-2 - Рогова Н. С. Наталья Сергеевна; Меркулов В. Г. Виктор Георгиевич; Рыжакова Н. К. Надежда Кирилловна; Борисенко А. Л. Алексей Леонидович (2010, 2010)
Заглавие с экрана